Analysis Internal Control Systems Of Mortgage - Laksmana, Aprin Arya; Iswanaji, Chaidir (Universitas Gorontalo, 2021)
The purpose of this research is to know directly about internal control system in the awarding of house ownership credits of PT. Bank Tabungan Negara Tbk. Magelang Branch Office. The type of research used is descriptive research with a qualitative approach to describing a phenomenon occurring. The results of the study showed that the procedure of giving ownership credit was executed according to procedures from the initial stage to the final stage. This is due to the operation of the internal control system well in accordance with the COSO standards which include the control environment, risk assessment, control activity, information and communication, and monitoring.